Development of a Rapid Immunodiagnostic Test for Pork Components in Raw Beef and Chicken Meats: a Preliminary Study - S N Depamede (Faculty of Animal Science, Bogor Agricultural University, 2011)
A rapid immunodiagnostic test that provides visual evidence of the presence of pork components in raw beef and chicken meats was developed. Colloidal gold was prepared and conjugated with anti-Swine IgG polyclonal antibody. Immunochromatographic test strips were produced, and then were used to test laboratory adulterated raw meat samples. The samples consisted of pork-in-beef, or pork-in-chicken at 1/0; 1/100; 1/1,000; 1/5,000; 1/10,000 (w/w) adulteration levels that were extracted in phosphate-buffered saline. Raw beef and chicken meats without pork were included as controls. Analysis was completed in 10 min. Detection limit was 1/5,000 (w/w), although 1/10,000 was also observed. This immunodiagnostic tests can be conveniently applied to detect low levels of pork components in raw beef and chicken meat products. For the commercial purposes, further studies need to be carried out.